The talk test as a measurement of exercise intensity in children’s natural movement patterns - Petersin, Bryana (My University, 2020)
The Talk Test (TT) has been shown to be a valid tool to subjectively measure exercise intensity in children while in a laboratory setting, but the TT has not been studied in a field setting with children’s natural play movements. The purpose of this study was to identify if the TT is an appropriate measure of exercise intensity during children’s real-world movement patterns. Specifically, this study looked at the TT as a measurement of exercise intensity in children ages 8 to 12. Eight children were recruited for this study. Subjects completed two sessions, one exercise TT was completed, in which subjects read The Pledge of Allegiance three times and responded whether they could speak comfortably. The second session consisted of the TT during 30 minutes of the subject’s natural physical activity play pattern. Chi-square analysis found a significant relationship in the children’s exercise field session between predicted ability to speak comfortably and observed ability to speak comfortably. This study found the TT to be a reliable and appropriate measure of intensity with children’s natural exercise patterns.
Keywords: Kinesiology; Exercise -- Physiological aspects; Respiration -- Measurement